Energy auditing of a typical residential building in Ibadan metropolis (2013)
An electricity audit of a building is the process whereby an energy manager survey and analyzes how energy is used in the building with the main objective of identifying opportunities for reducing the amount of energy used and ensuring that available energy is used efficiently. This study reports the outcome of an electricity audit on a typical residential building in a major location of Ibadan metropolis. The audited building is a four - flat apartment where all the customers in the building have different tariff plans. Two of the customers labeled Customer A and B are metered, while the other two Customers labeled C and D are not metered The result of the audit showed that the metered customers were paying the actual estimated electricity bills, while the non - metered customers were over billed by over 30 and 80% respectively. The study concluded by recommending the metering of all residential apartments and the use of pre - paid meters as it not only stimulate demand but also is more effective in the electricity billing process.